Medicare : preparing for the challenges of the 21st century - Reischauer, Robert D. (Robert Danton), 1941- (Distributed worldwide by Brookings Institution Press, 1998)
Papers presented at the ninth annual conference of the National Academy of Social Insurance, which was held in Washington, D.C., on Jan. 23-24, 1996.
Papers presented at the ninth annual conference of the National Academy of Social Insurance, which was held in Washington, D.C., on Jan. 23-24, 1996.
Keywords: Medicare; Medicare -- Congresses.; Medicare -- Forecasting -- Congresses.; Medicare.; Medicare -- Congrès.; Medicare -- Prévision -- Congrès.; MEDICAL -- Medicaid & Medicare.; Medicare -- Forecasting; Kongress; MEDICAL / Health Policy; Medicare -- Congresses; Medicare -- Forecasting -- Congresses; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings.; Actes de congrès.